2020
DOI: 10.3389/feart.2020.571700
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Short-Term Precursors of the Strong M > 7 Earthquakes in Southern California From the Simulated Stress–Strain State Patterns Exploiting Geomechanical Model and Seismic Catalog Data

Abstract: Since 2009, the stress-strain state (SS) of the earth's crust in Southern California region is being monitored through geomechanical modeling, taking into account the ongoing seismicity with magnitudes M > 1. Every new earthquake is assumed to cause a new defect in the earth's crust, leading to redistribution in the SS. With half-monthly SS updates, we found that the two strong earthquakes with M ∼ 7 that occurred in the area in 2010 and 2019 had been preceded by anomalies in the strength parameter D (indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…7a). Despite the relatively low amplitude 1 × 10 -4 , the last SD burst before the Ridgecrest earthquake described in (Bondur et al, 2020b;2020c) has the largest spatial dimensions. Besides the peak in EZ, SD intensity increase is observed along the entire length of the San Andreas fault from A1 to E5 (Fig.…”
Section: Stress-strain State Anomaliesmentioning
confidence: 99%
“…7a). Despite the relatively low amplitude 1 × 10 -4 , the last SD burst before the Ridgecrest earthquake described in (Bondur et al, 2020b;2020c) has the largest spatial dimensions. Besides the peak in EZ, SD intensity increase is observed along the entire length of the San Andreas fault from A1 to E5 (Fig.…”
Section: Stress-strain State Anomaliesmentioning
confidence: 99%
“…These anomalies manifested themselves as changes in the electron density profiles [11] and in changes in the total electron content (TEC) in the ionosphere in the Sumatra area [10]. At the same time, the use of a geomechanical model [18] for this region showed that the recorded increase in atmospheric pressure led to an increase in the stress-strain state of the Earth's crust and brought it closer to the strength limit before the Sumatra earthquake [10]. As an example of a non-tsunamigenic earthquake, let us consider the 52.5 m laser strainmeter recording from August 2000 (Figure 3, top).…”
Section: Registration Of Tsunamigenic Earthquakes Deformation Anomaliesmentioning
confidence: 99%
“…A series of Ridgecrest earthquakes, with magnitudes ranging from 5.4 to 7.1, occurred in Southern California during 4-6 July 2019, with the main 𝑀 7.1 shock of 6 July being one of the largest seismic events in this region in recent years. Given the dense population and the existing risk of strong and catastrophic earthquakes, the problem of seismic monitoring in Southern California has received noticeable attention [Clayton et al, 2015;Hutton et al, 2010]. At the same time, despite the huge amounts of seismological and geodetic data being collected in the region, the precursory patterns identification and short-term forecast still remains far from success.…”
Section: Introductionmentioning
confidence: 99%
“…The issues of short-term earthquake forecast have been widely researched for decades using various approaches, including the background seismicity analysis [Mogi, 1985;Molchan and Keilis-Borok, 2008], search and detection of various geophysical precursors [Sobolev and Ponomarev, 2003], and satellite-based monitoring techniques [Akopian et al, 2017;Bondur and Zverev, 2005;Bondur et al, 2007Bondur et al, , 2018]. An important contribution is made with implementation of high-detail geomechanical models [Bondur et al, 2016], taking into account the current state of the crust in the studied region. This approach allows overcoming the problem of weak manifestation of deep stress accumulation and deformation processes on the Earth's surface, which complicates their detection by means of direct monitoring techniques [Bondur et al, 2020a].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation